Pengaruh Konsentrasi Nutrisi AB MIX Terhadap Pertumbuhan dan Hasil Tiga Varietas Pakcoy (Brassica rapa L.) pada Hidroponik Sistem Sumbu - Erpiana, Lia; Nurmayulis, Nurmayulis; Muztahidin, Nur Iman; Rohmawati, Imas (Jurnal Agroekoteknologi, 2024)
This study aimed to determine the effect of AB Mix nutrient concentration on the growth and yield of three varieties of pakcoy. This study was carried out form April to May 2024 at Manjun Village, Rancabuaya Village, Jambe District, Tangerang Regency, Banten Province. The study was structured in a Randomized Group Design with two factors. The first factor is the nutrient concentration of AB Mix consisting of three levels : P1= 15 ml/l, P2= 20 ml/l, and P3= 25 ml/l. The second factor is that the pakcoy variety consists of three levels: V1 = Pakcoy variety Nauli F1, V2 = Pakcoy variety Flamingo F1, and V3 = Pakcoy variety Emone-26. The study results showed that P1 treatment gave the best results in the parameters of plant height, plant fresh weight and root shoot ratio. The V3 treatment showed the best results in the parameter of plant height, while the V1 showed the best results in the number of leaves parameter. There was no interaction between AB Mix concentration and pakcoy varieties on all observed parameters. Gived AB Mix with a concentration of 15 ml/l can provide the best growth for pak choy plants. The Pakcoy Emone-26 and Nauli F1 varieties have the best plant growth.